Adaptations of Calvinism in Reformation Europe: essays in honour of Brian G. Armstrong - Armstrong, Brian G.; Holt, Mack P. ca. 20./21. Jh. (St. Andrews studies in Reformation history, 2007)
pt. 1. Calvin, Beza, and Geneva -- pt. 2. Reformed ideas outside Geneva -- pt. 3. The Reformation in France -- pt. 4. The Reformations in England and Scotland